Children's Exploration and Cultural Formation - Hedegaard, Mariane; Eriksen Ødegaard, Elin (International Perspectives on Early Childhood Education and Development,, 2020)
This open access book examines the educational conditions that support cultures of exploration in kindergartens. It conceptualises cultures of exploration, whether those cultures are created through children's own engagement or are demanded of them through undertaking specific tasks within different institutional settings. It shows how the conditions for children's exploration form a web of activities in different settings with social relationships, local landscapes and artefacts. The book builds on the understanding of cultural traditions as deeply implicated in the developmental processes, meaning that local considerations must be reflected in education for sustainable futures. Therefore the book examines and conceptualises exploration and cultural formation through locally situated cases and navigates toward global educational concepts. The book provides different windows into how children may explore in everyday practice settings in kindergarten, and contributes to a loci-based,ecological, integral knowledge relevant for early childhood education.